2002
DOI: 10.1001/jama.287.5.628
|View full text |Cite
|
Sign up to set email alerts
|

Medical Management of Advanced Heart Failure

Abstract: Current management of advanced heart failure is based more on consensus than on randomized trials. Systematic investigation should address not only new therapies but also strategies for selecting and optimizing therapies already available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
213
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(224 citation statements)
references
References 98 publications
2
213
0
9
Order By: Relevance
“…3,4 Nitrates are powerful NO donors that are frequently administered to patients with acute heart failure. 5 Low-dose NTG administration primarily results in venodilation, thus lowering cardiac filling pressures, increasing the pressure gradient for myocardial perfusion, and decreasing myocardial oxygen demand. 1,6,7 Recent guidelines recommended the use of vasodilators, including NTG, in order to achieve haemodynamic and symptomatic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Nitrates are powerful NO donors that are frequently administered to patients with acute heart failure. 5 Low-dose NTG administration primarily results in venodilation, thus lowering cardiac filling pressures, increasing the pressure gradient for myocardial perfusion, and decreasing myocardial oxygen demand. 1,6,7 Recent guidelines recommended the use of vasodilators, including NTG, in order to achieve haemodynamic and symptomatic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Profile C (cold and congested) is second in frequency, being described in approximately 20.0% of patients, followed by profile L (cold and dry), 3.5% [11][12][13] . In our hospital, a referral center for the treatment of heart failure, the numbers are substantially different, being C the most frequently identified profile, in approximately 65.0% of hospitalized patients.…”
Section: Fig 2 -Mortality According the Cardiomyopathy Etiology -Chamentioning
confidence: 97%
“…In a study published in 2003, Stevenson et al demonstrated that patients with profile C were those who had the poorest performance among patients admitted with decompensated HF [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…For triage and initiation of therapy at the time of admission, patients may be categorized functionally as having clinically adequate perfusion (wet and warm) or evidence of low resting perfusion (wet and cold), usually suspected because of a narrow pulse pressure, cold extremities, or both. 23,24 The "wet and cold" patients with clinical evidence of low perfusion have longer hospital stays and higher numbers of subsequent events. 25 Current consensus is that such patients generally require therapy in addition to diuretics to restore compensation.…”
Section: Congestion and Apparent Hypoperfusionmentioning
confidence: 99%